"The relationship of social responsibility and excellence of the public sector in achieving sustainable development of society. "Case Study of the Department of Land and Survey - Al - Aatharbah, ‏​‏​‏​​‏​‏​​‏​‏​‏​‏​‏​‏ Ghassan Awad (Arab Journal for Sciences and Research Publishing, 2017)
The study aimed to investigate the relationship of social responsibility and excellence of the public sector in achieving sustainable development, and to know the relevance of social responsibility and excellence to internal and external environment for Land and Survey Department in sustainable development achievement in Jordan society. T0 achieve this goal the study data was collected from a random sample totalling 120 employees. , Leaders were selected as purposive sample amounting (10), within the sample to investigate the importance of sustainable development from their perspective because they develop strategies of public policies related to national national agenda and government trends within all working methodologies. The study used questionnaire as a tool to gather information. The study found that there is an impact of CSR on excellence and also found the that there is a relationship between social responsibility and sustainable development as well as having the effect of excellence on sustainable development. The study recommended the management of land and Survey Department to empower staff; in order to enhance the work environment and the application of the principle of equality of opportunity and to authorize powers. And to review the laws and legislation that govern department work in line with national developments and aspirations in Jordan, and enhance the investment climate for investors, whether internal or external; in order to support economic development in Jordan.
Keywords: Corporate Social Responsibility; Sustainable Development; Indoor Environment; Outdoor Environment